Inositol polyphosphate 4-phosphatase II regulates PI3K/Akt signaling and is lost in human basal-like breast cancers - Fedele, Clare G.; Ooms, Lisa M.; Ho, Miriel; Vieusseux, Jessica; O'Toole, Sandra A.; Millar, Ewan K.; Lopez-Knowles, Elena; Sriratana, Absorn; Gurung, Rajendra; Baglietto, Laura; Giles, Graham G.; Bailey, Charles G.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Inositol polyphosphate 4-phosphatase-II (INPP4B) is a regulator of the phosphoinositide 3-kinase (PI3K) signaling pathway and is implicated as a tumor suppressor in epithelial carcinomas. INPP4B loss of heterozygosity (LOH) is detected in some human breast cancers; however, the expression of INPP4B protein in breast cancer subtypes and the normal breast is unknown. We report here that INPP4B is expressed in nonproliferative estrogen receptor (ER)-positive cells in the normal breast, and in ER-positive, but not negative, breast cancer cell lines. INPP4B knockdown in ER-positive breast cancer cells increased Akt activation, cell proliferation, and xenograft tumor growth. Conversely, reconstitution of INPP4B expression in ER-negative, INPP4B-null human breast cancer cells reduced Akt activation and anchorage-independent growth. INPP4B protein expression was frequently lost in primary human breast carcinomas, associated with high clinical grade and tumor size and loss of hormone receptors and was lost most commonly in aggressive basal-like breast carcinomas. INPP4B protein loss was also frequently observed in phosphatase and tensin homolog (PTEN)-null tumors. These studies provide evidence that INPP4B functions as a tumor suppressor by negatively regulating normal and malignant mammary epithelial cell proliferation through regulation of the PI3K/Akt signaling pathway, and that loss of INPP4B protein is a marker of aggressive basal-like breast carcinomas.